'Doing' gender in a rural Scottish secondary school: an ethnographic study of classroom interactions. Issue 4 (2nd October 2018) - Menzies, Fiona G.; Santoro, Ninetta
ABSTRACT: This article draws on data from an ethnographic case study that examined how pupils' gendered identities are constructed in one rural secondary school in Scotland. We utilise the work of Michel Foucault and Judith Butler to provide theoretical insight into how and why pupils take up particular gendered positions in school, focusing on the influence of teacher–pupil interactions. The findings suggest that some teachers reinforce traditional constructs of masculinities and femininities, and fail to disrupt boys' views of girls as objects of desire. Teachers are also seen to reinforce gender stereotypes in their understandings of the rural landscape as an exclusive site for constructing masculine identities. We claim that this potentially limits pupils' educational experiences. We conclude by suggesting that there is a need for teachers to develop deeper, more sophisticated understandings of gender, an area currently neglected in Scottish educational policy and teacher education programmes.